Short-term exposure to ambient fine particulate matter and psoriasis: A time-series analysis in Beijing, China - Wu, Junhui; Chen, Hongbo; Yang, Ruotong; Yu, Huan; Shang, Shaomei; Hu, Yonghua (Frontiers in Public Health, 2022)
Background: Ambient fine particulate matter (PM2.5) adversely affects human health and has been linked to a variety of skin disorders. However, little is known about the effects of PM2.5 on psoriasis. Methods: The Beijing Medical Claim Data for Employees database recorded 500,266 outpatient visits for psoriasis during 2010-2017. A generalized additive quasi-Poisson model was used to examine the relationship between daily PM2.5 concentrations and outpatient visits for psoriasis with stratification by sex, age, and season. Results: Short-term exposure to PM2.5 was associated with outpatient visits for psoriasis-related health concerns. A same-day increase of 10 μg/m3 in PM2.5 concentrations was associated with a 0.29% (95% confidence interval: 0.26%–0.32%) increase in daily outpatient visits for psoriasis. Female and older patients appeared to be more sensitive to the effects of PM2.5 (P < 0.05). Conclusions: Short-term elevations in PM2.5 concentrations may be associated with exacerbations in psoriasis. Further work is warranted to confirm the findings and elucidate the underlying biological mechanisms.